2016
DOI: 10.1136/jim-2015-000047
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Esophageal Varices and Variceal Hemorrhage in Patients with Acute Upper Gastrointestinal Bleeding

Abstract: In patients with upper gastrointestinal bleeding (UGIB), identifying those with esophageal variceal hemorrhage prior to endoscopy would be clinically useful. This retrospective study of a large cohort of patients with UGIB used logistic regression analyses to evaluate the platelet count, aspartate aminotransferase (AST) to platelet ratio index (APRI), AST to alanine aminotransferase (ALT) ratio (AAR) and Lok index (all non-invasive blood markers) as predictors of variceal bleeding in (1) all patients with UGIB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 33 publications
0
21
0
3
Order By: Relevance
“…Low platelet counts, high bilirubin level, presence of ascites, severity of cirrhosis (CTP-A, and CTP-B) were found to have predictive ability on univariate analysis. Earlier studies (2,4,(15)(16)(17) have also shown an independent predictive ability of low platelet count in liver cirrhosis patients to predict LEVx.…”
Section: Discussionmentioning
confidence: 86%
“…Low platelet counts, high bilirubin level, presence of ascites, severity of cirrhosis (CTP-A, and CTP-B) were found to have predictive ability on univariate analysis. Earlier studies (2,4,(15)(16)(17) have also shown an independent predictive ability of low platelet count in liver cirrhosis patients to predict LEVx.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have found that serum markers of liver fibrosis have moderate value for predicting liver cirrhosis in patients with HBV infection[29,30]. However, there is disagreement on the performance of serum markers of liver fibrosis in EV or HRV prediction[8,19,31]. In this study, we found that APRI and FIB-4 could not predict HRV.…”
Section: Discussionmentioning
confidence: 49%
“…Serum markers of liver fibrosis such as PLT count, aspartate aminotransferase (AST)-to-PLT ratio index (APRI), Fibrosis-4 (FIB-4), and the Lok index are useful in predicting severe liver fibrosis or cirrhosis[16-18], EV risk, and variceal bleeding risk in patients with HBV infection[19]. It remains unknown whether these serum markers of liver fibrosis can identify patients without HRV among those who do not meet the Baveno VI criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Es ist sehr schwierig, bei Patienten mit oberer gastrointestinaler Blutung aufgrund der Anamnese und anderer nicht-invasiver Indikatoren zwischen variköser und nicht-variköser Blutungsquelle zu unterscheiden. In einer großen retrospektiven Analyse von 2233 stationär aufgenommenen Patienten mit oberer gastrointestinaler Blutung, davon 1034 Patienten mit Leberzirrhose, waren Thrombozytopenie, AST-Thrombozyten-Ratio (APRI-Score), AST-ALT-Ratio (AAR) und der Lok-Index (nicht-invasive Labortests) hinweisend auf das Vorhandensein von Varizen sowie mit niedrigerer Sensitivität und Spezifität auch hinweisend auf eine Varizenblutung [6]. Leider war keiner der untersuchten Parameter in multivariaten Untersuchungen in der Lage, bei Patienten mit bekannter Leberzirrhose sicher zwischen nicht-varikösen und varikösen Blutungen zu unterscheiden [6].…”
Section: Aussageunclassified
“…In einer großen retrospektiven Analyse von 2233 stationär aufgenommenen Patienten mit oberer gastrointestinaler Blutung, davon 1034 Patienten mit Leberzirrhose, waren Thrombozytopenie, AST-Thrombozyten-Ratio (APRI-Score), AST-ALT-Ratio (AAR) und der Lok-Index (nicht-invasive Labortests) hinweisend auf das Vorhandensein von Varizen sowie mit niedrigerer Sensitivität und Spezifität auch hinweisend auf eine Varizenblutung [6]. Leider war keiner der untersuchten Parameter in multivariaten Untersuchungen in der Lage, bei Patienten mit bekannter Leberzirrhose sicher zwischen nicht-varikösen und varikösen Blutungen zu unterscheiden [6]. Derzeit werden weitere Verfahren evaluiert; beispielsweise scheinen sowohl die Lebersteifigkeit, gemessen über transiente Elastografie (Fibroscan ® , Fa.…”
Section: Aussageunclassified